MINAT BELI ULANG PENERBANGAN KOMERSIL DI KALIMANTAN TIMUR - Muhammad Awaluddin (AKUNTABEL, 2013)
The repeat purchase intentions changes in the number of passengers was triggered partly by. It will be interesting to see, because the high-low factor in consumer decision making repeated purchases will have an impact on the profit for the airline in question. The number of airline companies in Indonesia either young age, or who should have been categorized established flight hours due to high market ups and downs even airlines ceased to operate due to compete in that market. In addition to the impact on repeat purchases sacrifices they have to do the sacrifice which so far does not seem fair that they spend between values with the value they get. Why there is a difference to re-purchase a ticket on any airline , whereas under Regulation issued by the Minister of Transportation, it was clear that the rules that must be met by all the airlines in which the rules related to the age of the aircraft, limit the number of landings, upper rate limit, and the limit lower rates are the same among all airlines operating in Indonesian, where the rules were made to support the comfort and safety of passengers so that passengers are not harmed by the airlines.Keywords: Repeat Purchase; Consumer Satisfaction; Commercial Flight